The effect of polymorphisms in FSHR and FSHB genes on ovarian response: a prospective multicenter multinational study in Europe and Asia. Issue 6 (23rd April 2021) - Polyzos, Nikolaos P; Neves, A R; Drakopoulos, P; Spits, C; Alvaro Mercadal, B; Garcia, S; Ma, P Q M; Le, L H; Ho, M T; Mertens, J; Stoop, D; Tournaye, H; et al.
Abstract: STUDY QUESTION: Does the presence of single nucleotide polymorphisms (SNPs) in the FSH receptor gene ( FSHR) and/or FSH beta subunit-encoding gene ( FSHB ) influence ovarian response in predicted normal responders treated with rFSH? SUMMARY ANSWER: The presence of FSHR SNPs (rs6165, rs6166, rs1394205) has a statistically significant impact in ovarian response, although this effect is of minimal clinical relevance in predicted normal responders treated with a fixed dose of 150 IU rFSH. WHAT IS KNOWN ALREADY: Ovarian reserve markers have been a breakthrough in response prediction following ovarian stimulation. However, a significant percentage of patients show a disproportionate lower ovarian response, as compared with their actual ovarian reserve. Studies on pharmacogenetics have demonstrated a relationship between FSHR or FSHB genotyping and drug response, suggesting a potential effect of individual genetic variability on ovarian stimulation. However, evidence from these studies is inconsistent, due to the inclusion of patients with variable ovarian reserve, use of different starting gonadotropin doses, and allowance for dose adjustments during treatment. This highlights the necessity of a well-controlled prospective study in a homogenous population treated with the same fixed protocol. STUDY DESIGN, SIZE, DURATION: We conducted a multicenter multinational prospective study, including 368 patients from Vietnam, Belgium, and Spain (168 from Europe and 200 from Asia), from November 2016 until June 2019. All patients underwent ovarian stimulation followed by oocyte retrieval in an antagonist protocol with a fixed daily dose of 150 IU rFSH until triggering. Blood sampling and DNA extraction was performed prior to oocyte retrieval, followed by genotyping of four SNPs from FSHR (rs6165, rs6166, rs1394205) and FSHB (rs10835638). PARTICIPANTS/MATERIALS, SETTING, METHODS: Eligible were predicted normal responder women <38 years old undergoing their first or second ovarian stimulation cycle. Laboratory staff and clinicians were blinded to the clinical results and genotyping, respectively. The prevalence of hypo-responders, the number of oocytes retrieved, the follicular output rate (FORT), and the follicle to oocyte index (FOI) were compared between different FSHR and FSHB SNPs genotypes. MAIN RESULTS AND THE ROLE OF CHANCE: The prevalence of derived allele homozygous SNPs in the FSHR was rs6166 (genotype G/G) 15.8%, rs6165 (genotype G/G) 34.8%, and rs1394205 (genotype A/A) 14.1%, with significant differences between Caucasian and Asian women ( P < 0.001). FSHB variant rs10835638 (c.-211 G>T) was very rare (0.5%). Genetic model analysis revealed that the presence of the G allele in FSHR variant rs6166 resulted in less oocytes retrieved when compared to the AA genotype (13.54 ± 0.46 vs 14.81 ± 0.61, estimated mean difference (EMD) −1.47 (95% CI −2.82 to −0.11)). In FSHR variant rs1394205, a significantly lower number of oocytes was retrieved in patients with an A allele when compared to G/G (13.33 ± 0.41 vs 15.06 ± 0.68, EMD −1.69 (95% CI −3.06 to −0.31)). A significantly higher prevalence of hypo-responders was found in patients with the genotype A/G for FSHR variant rs6166 (55.9%, n = 57) when compared to A/A (28.4%, n = 29), ORadj 1.87 (95% CI 1.08–3.24). No significant differences were found regarding the FORT across the genotypes for FSHR variants rs6166, rs6165, or rs1394205. Regarding the FOI, the presence of the G allele for FSHR variant rs6166 resulted in a lower FOI when compared to the A/A genotype, EMD −13.47 (95% CI −22.69 to −4.24). Regarding FSHR variant rs6165, a lower FOI was reported for genotype A/G (79.75 ± 3.35) when compared to genotype A/A (92.08 ± 6.23), EMD −13.81 (95% CI −25.41 to −2.21). LIMITATIONS, REASONS FOR CAUTION: The study was performed in relatively young women with normal ovarian reserve to eliminate biases related to age-related fertility decline; thus, caution is needed when extrapolating results to older populations. In addition, no analysis was performed for FSHB variant rs10835638 due to the very low prevalence of the genotype T/T (n = 2). WIDER IMPLICATIONS OF THE FINDINGS: Based on our results, genotyping FSHR SNPs rs6165, rs6166, rs1394205, and FSHB SNP rs10835638 prior to initiating an ovarian stimulation with rFSH in predicted normal responders should not be recommended, taking into account the minimal clinical impact of such information in this population. Future research may focus on other populations and other genes related to folliculogenesis or steroidogenesis. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by an unrestricted grant by Merck Sharp & Dohme (MSD). N.P.P. reports grants and/or personal fees from MSD, Merck Serono, Roche Diagnostics, Ferring International, Besins Healthcare, Gedeon Richter, Theramex, and Institut Biochimique SA (IBSA). N.L.V. and M.T.H. report consultancy and conference fees from Merck, Ferring, and MSD, outside the submitted work. P.D. has received honoraria for lecturing and/or research grants from MSD, Ferring International, and Merck. D.S. reports grants and/or personal fees from MSD, Ferring International, Merck Serono, Cook, and Gedeon Richter. A.R.N., B.A.M., C.S., J.M., L.H.L., P.Q.M.M., H.T., and S.G. report no conflict of interests. TRIAL REGISTRATION NUMBER: NCT03007043